Climate-Smart Agriculture in Ethiopia - International Center for Tropical Agriculture; United States Agency for International Development (International Center for Tropical Agriculture, 2017)
The agriculture sector is the backbone of Ethiopia’s economy and livelihoods. Yet, heavy reliance on rain-fed systems has made the sector particularly vulnerable to variability in rainfall and temperature. Climate change may decrease national gross domestic product (GDP) by 8–10% by 2050, but adaptation action in agriculture could cut climate shock-related losses by half. • Climate risk management interventions and long-term adaptation actions need to match localized vulnerabilities and impacts. The drought-prone highland areas are likely to experience more intense and irregular rainfall, affecting yields of slow maturing, long-cycle crops; however, the higher altitude moisture-sufficient parts of the highlands where cereal production is dominant are expected to increase in suitability and productivity of some cereals. Increased temperatures and extended drought periods are likely to negatively affect the lowlands, posing particular challenges to already vulnerable pastoral and agropastoral populations. • Smallholder farmers produce over 90% of the agricultural output in Ethiopia. Despite high usage of traditional production methods, there is evidence of increased use of organic fertilizers, adoption of crop varieties with higher resistance/tolerance to drought, pests, and diseases, and improved livestock feeding practices, as attempts to increase productivity and resilience, but also with cobenefits in terms of reducing agricultural greenhouse gas (GHG) emissions. • Given the country’s poverty and food insecurity challenges, priorities for economic growth and increased resilience have pushed mitigation efforts backstage. Less than one-fifth of the climate finance is directed to mitigation efforts, mostly through renewable energy. Increased investments in agricultural practices that bring about mitigation co-benefits would bring out agriculture’s role as a lead sector in low-emissions development. • A large proportion of the country’s land area is undergoing some form of soil erosion or land degradation, hence CSA-related efforts have been focused on restoring degraded lands through soil and water conservation measures, agroforestry, farmer-managed natural regeneration (FMNR), area closures, and dissemination of improved varieties. Such CSA practices and technologies are largely supported by the government and its development partners, through research and development, rural extension and advisory services as well as direct implementation. Many of these practices are implemented within the framework of the integrated watershed management approach through projects such as the Sustainable Land Management Programme (SLMP). • Adoption levels of some CSA practices and technologies, such as conservation agriculture and agroforestry, among smallholder farmers remain low. Increased public and private support to enable access to improved inputs, equipment, credit and insurance schemes is needed to boost farmers’ ability to manage risks and invest in long-term climate actions. • Highly fragmented land units are not suited for effective implementation of some CSA practices, while land tenure regimes can significantly hinder credit access for smallholders. Ethiopia has made great effort to issue land certificates to smallholder farmers, and such programmes should be accompanied by sensitization of farmers and microfinance providers on the costs and benefits of investing in on-farm climate-smart and sustainable land management practices. • Through an ambitious policy framework built largely on the Climate Resilient Green Economy (CRGE) Strategy and an enabling institutional infrastructure, Ethiopia has taken major steps towards mainstreaming climate change into agricultural planning. To demonstrate its unwavering commitments to green growth and food security and operationalize strategies and plans, additional national and international resources need to be mobilized over the next years, to fill existing financial gaps.